2020
DOI: 10.31234/osf.io/gvr6m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Do We Need Neural Models to Explain Human Judgments of Acceptability?

Abstract: Native speakers can judge whether a sentence is an acceptable instance of their language. Acceptability provides a means of evaluating whether computational language models are processing language in a human-like manner. We test the ability of language models, simple language features, and word embeddings to predict native speakers’ judgments of acceptability on English essays written by non-native speakers. We find that much sentence acceptability variance can be captured by a combination of misspellings, wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Another explanation for the current lower performance for our embedding models relates to the knowledge structures in BERTs. Previously, studies indicated that for BERTs, the mid-layers have the best performance in syntactic-related tasks (Kelly et al, 2020). Such results may indicate that, unlike previous statistical models that reach the highest performance in output layers, embeddingbased models like BERTs may store different types of knowledge across different layers: the deeper the layers are, the more abstract concepts they will store.…”
Section: Statistical Vs Embedding Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…Another explanation for the current lower performance for our embedding models relates to the knowledge structures in BERTs. Previously, studies indicated that for BERTs, the mid-layers have the best performance in syntactic-related tasks (Kelly et al, 2020). Such results may indicate that, unlike previous statistical models that reach the highest performance in output layers, embeddingbased models like BERTs may store different types of knowledge across different layers: the deeper the layers are, the more abstract concepts they will store.…”
Section: Statistical Vs Embedding Modelsmentioning
confidence: 97%
“…Compared to state-of-the-art native language identifiers relying on statistical methods (such as Ngrams) with F-scores above 0.85, the performance of embedding models is still worse. Previous studies (Vajjala and Banerjee, 2017;Jing et al, 2020) argued that such worse predictions from embedding models indicate embedding models might have a stronger ability in capturing semantic information; while statistical-based language models might have better performance in capturing morphosyntactic and syntactic information.…”
Section: Statistical Vs Embedding Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…There have been several studies on linguistic acceptability in English over the last years, using various forms of neural networks, targeting different error types, and focusing on different underlying aims. Neural networks trained to make acceptability judgements can yield for example theoretical insights into how language is perceived and acquired (Lawrence et al, 2000;Lau et al, 2017), or into what knowledge language models represent (Linzen et al, 2016;Jing et al, 2019). Practical applications of such models include evaluation of results from language-generating systems (such as question-answering or machine translation) or providing assistance in language learning.…”
Section: Introductionmentioning
confidence: 99%